Cicatrização cutânea em Piaractus mesopotamicus suplementados com carboquelato de cromo e Saccharomyces cerevisiae - Bortoluzzi, Neida Lucas [UNESP]; Castro, Marcelo Pardi de [UNESP]; Claudiano, Gustavo da Silva [UNESP]; Yunis-Aguinaga, Jefferson [UNESP]; Cueva-Quiroz, Victor Alexander [UNESP]; Moraes, Julieta Rodini Engrácia de [UNESP]; Moraes, Flávio Ruas de [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2017)
Wound healing and tissue repair are necessary to ensure survival and health of any organism. The aim of this study was to investigate the impact of supplementation with chromium carbochelate (CC) and Saccharomyces cerevisiae (SC) on wound healing in tropical teleost fish Piaractus mesopotamicus. Thus, fish were distributed into four groups: a) control (without supplementation); b) supplemented with 18 mg/kg of chromium carbochelate; c) supplemented with 0.3% of S. cerevisiae and d) supplemented with an association of both supplements. After 105 days of feeding, full-thickness skin incisions (2.0 x 1.0 x 0.25 cm) were performed removing epidermis and dermis. Macroscopic and histologic observations were carried out at 1, 3, 7, 14, 21, 28, and 35 days after wounding to monitor the healing rate. Opposing fronts advanced gradually and faster each day demonstrating a progressive increase in the healing process over time. The inflammatory process was exacerbated and expansive, with an increase in mucous cells and chromatophores. Although no significant differences were observed between groups on wound retraction and microscopic parameters, fish supplemented with CC and SC showed faster re-epithelialization, greater degree of organization of collagen fibers, and higher neovascularization. We concluded that supplementation with S. cerevisiae and chromium carbochelate improves specific aspects of cutaneous healing process in pacu.
Wound healing in Piaractus mesopotamicus supplemented with chromium carbochelate and Saccharomyces cerevisiae
Keywords: Chromium carbochelate; Freshwater fish; Pacu; Saccharomyces cerevisiae; Tissue repair